Breastfeeding, Walking Onset, and Abdominal Obesity Are Determinants of Physical Fitness among Latin American and Spanish Schoolchildren: A Cross-Cultural Study - Karina E. Andrade-Lara; José Carlos Cabrera Linares; Juan Antonio Párraga Montilla; Alexander Mayanquer-Lara; Manuel Lucena Zurita; Pedro Ángel Latorre Román (MDPI AG, 2024)
Objective: To comp+are levels of physical fitness between Ecuador and Spain and identify whether breastfeeding period, walking onset, and abdominal obesity are determinants of physical performance in schoolchildren from Ecuador and Spain. Methods: a total of 352 schoolchildren (6-12 years old) from Ecuador (n = 176) and Spain (n = 176) joined in this study. Anthropometric measures, socio-demographic characteristics, and physical fitness were evaluated. Results: Spanish schoolchildren showed better performance in handgrip strength, standing long jump, and 25 m sprint (p = 0.021; p < 0.001; p < 0.001; p < 0.001, respectively). Furthermore, Spanish children showed better cardiorespiratory fitness (p < 0.001) and a higher <semantics>VO2</semantics> max (p = 0.002) with regards to their peers. In addition, children from Ecuador and Spain showed an influence of breastfeeding period (p ranged from <0.001 to 0.043) and walking onset (p ranged from <0.001 to 0.032) on physical performance. Moreover, physical fitness components were protective factors of abdominal obesity in Ecuadorian and Spanish schoolchildren (p ranged from =0.001 to 0.049). Conclusions: Our findings revealed the influence of the infancy period and the onset of walking on children's physical performance, highlighting the importance of these factors in motor development during early childhood and also their influence in middle childhood and throughout adulthood.